A study of the Malayalee- Qatar Diaspora: Cultural Identity and media consumption - Jinu Jacob and Ms.Manjula Venkataraghavan (Global Media Journal, Indian Edition, 2018)
Media plays an important role in the reconstruction of cultural identities of the diaspora and helps negotiate a borderline existence between the home country and the host country. The diasporic identity is constructed through the use of media and the identity that they carried with them to the new host country. The polarities of the physical connection to the place that they currently stay in and the cultural bond that they share with their native nation constantly tug at them. Media helps in maintaining the constancy in the diasporic identity. Accessibility of ethnic media is a way of maintaining the traditional links with their homeland as it serves as a symbolic bond connecting their cultures to their places of origin which is partly imagined and partly experienced. They form communities to revive memories of the past and strive to achieve a closure to their floating lives through their media practices ( Shi, 2005). Media's influence on cultural identity has been studied in various diaspora settings, but, very few pieces of research have focused on the Indian diaspora in other countries, particularly the Malayalees settled in the Gulf countries. This paper aims to examine the media consumption pattern of the Malayalee Diaspora in Qatar, its relation to the cultural identities of the diaspora and the influence of the changing media environment. The study will use a mixed method approach, adopting both survey and in-depth interview for a deeper understanding of the pattern of responses.